Inter-Format Competition among Retailers - The Role of Private Label Products in Market Delineation - Dennis Rickert; Christian Wey; Justus Haucap; Ulrich Heimeshoff; Gordon J. Klein (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Given various recent antitrust investigations on the retail sector, we deal with uncovering demand systems substitution patterns for a particular market (diapers) to investigate the inter-format competition (supermarkets vs. discounters vs. drugstores). Using the uncovered demand system we compute retail and manufacturer margins and combine those with standard market delineation techniques, showing that the strongest substitution patterns are between the leading brand as well as private labels sold at drugstores and discounters. This result is important given controversies among competition authorities, firms and academic researchers.
Keywords: L40; L81; C50; 330